Preslavisms in the Аpocryphal Questions of Bartholomew - Chromá, Martina (Studia Ceranea, 2014)
Paper deals with the lexical analysis of the Old Church Slavonic version of the Apocryphal Questions of Bartholomew, a literary monument written most likely in Greek in the 3rd century. The analysis shows that the Slavonic version contains not only lexical elements typical for the Preslav redaction, but also some archaic figures. This leads to the conclusion, that the primal Old Church Slavonic translation may be made in Bulgaria in the 10th century. There are two possibilities of a more exact dating. The text may have been translated in the early 10th century when the lexical elements of the Preslav redaction weren’t strictly used yet and still there occurred many archaic figures. The second possibility is that the translation was made later in the 10th century in one of the distant centers of the Preslav literary school, in which a specific tradition in using Preslav and archaic lexical elements was held. However, a further lexical and language analysis is needed for the confirmation of the stated dating.